EFEKTIVITAS MODEL PEMBELAJARAN COOPERATIVE INTEGRATED READING AND COMPOSITION (CIRC) TERHADAP LITERASI IPS KELAS V SD - Arafli, Faris Maulana; Kurniawati, Rissa Prima; Mersina Mursidik, Elly’s (Jurnal Perseda : Jurnal Pendidikan Guru Sekolah Dasar, 2025)
Social Studies literacy is crucial for shaping students' ability to understand and analyze social issues. However, observations at Terung Elementary School's 5th grade indicate low levels of both Social Studies literacy and student interest. This situation is exacerbated by conventional teaching methods that inadequately engage students. Student interest is a critical factor influencing comprehension of the material. Therefore, an innovative and engaging teaching model, such as the Cooperative Integrated Reading and Composition (CIRC) model, is needed. This study aims to assess the effectiveness of the CIRC model on Social Studies literacy among 5th-grade students. It employs a quantitative method with a quasi-experimental post-test only control group design. The study population consists of all 5th-grade students in Panekan District, Magetan Regency, with a sample of 40 students divided into 20 in the experimental group and 20 in the control group. Data collection techniques include post-tests and interest surveys. The research findings demonstrate a significant difference between the experimental and control groups. This is evidenced by an independent sample t-test yielding a significance value of 0.000 < 0.05, indicating that the CIRC teaching model significantly improves students' Social Studies literacy. Thus, the CIRC model is effective in enhancing Social Studies learning outcomes for 5th-grade elementary school students.